First-in-man Study With Inclacumab, a Human Monoclonal Antibody Against P-selectin. Issue 6 (June 2015) - Schmitt, Christophe; Abt, Markus; Ciorciaro, Cornelia; Kling, Dorothee; Jamois, Candice; Schick, Eginhard; Solier, Corinne; Benghozi, Renée; Gaudreault, Jacques
Abstract : Abstract: Inclacumab, a novel monoclonal antibody against P-selectin in development for the treatment and prevention of atherosclerotic cardiovascular diseases, was administered in an ascending single-dose study as intravenous infusion to evaluate safety, pharmacokinetics, and pharmacodynamics. Fifty-six healthy subjects were enrolled in this randomized, double-blind placebo-controlled study. Each dose level (0.03–20 mg/kg) was investigated in separate groups of 8 subjects (6 on inclacumab, 2 on placebo). Platelet–leukocyte aggregates, free/total soluble P-selectin concentration ratio, drug concentrations, bleeding time, platelet aggregation, antibody formation, and routine laboratory parameters were measured frequently until 32 weeks. Pharmacokinetic profiles were indicative of target-mediated drug disposition. Platelet–leukocyte aggregate inhibition and soluble P-selectin occupancy showed dose dependency and were strongly correlated to inclacumab plasma concentrations, with IC50 of 740 and 4600 ng/mL, respectively. Inclacumab was well tolerated by the majority of subjects and did neither affect bleeding time nor platelet aggregation. These findings allowed the investigation of the potential beneficial therapeutic use of inclacumab in patient study.